Primary plasma cell leukemia: A rare case report (Indian Journal of Case Reports, 2019)
Plasma cell leukemia (PCL) is a rare form of plasma cell dyscrasia. Between 2% and 4% of malignant PCD cases are PCL. The presentation may be primary, de novo, or secondary, evolving from an existing case of myeloma as part of the terminal phase of the disease. The median age of patients is 50-60 years with an equal incidence in males and females. Here, we report a case of primary PCL, presenting at the age of 62 years.